2011
DOI: 10.1097/tp.0b013e3182115ba2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of the Acquisition of Cytomegalovirus-Specific Immune Response During Preemptive Treatment

Abstract: Our results demonstrate that preemptive therapy is a safe and an effective strategy for the control of CMV infection in solid-organ transplant recipients at high risk for CMV infection. This is the first study that reports a therapeutic effect of the acquisition of CMV-specific immune response during preemptive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 32 publications
3
27
1
1
Order By: Relevance
“…The authors concluded that baseline immunity and antiviral therapy but not antithymocyte globulin treatments profoundly influence T-cell reconstitution in kidney transplant recipients. Another study of 21 subjects on preemptive therapy after SOT, who developed CMV replication episodes at a median of 4 weeks (range 2-8 weeks) after transplantation and a CMV-specific T-cell response (as determined by CMV-specific T-cell intracellular cytokine Kotton staining) at a median of 12 weeks (range 10-20 weeks), experienced a decline in the incidence of CMV replication episodes that was inversely correlated with the acquisition of the CMV-specific T-cell response (42). In addition, after acquisition of the immune response, 42 CMV replication episodes were cleared without treatment.…”
Section: Vaccines and Tailored Prevention Based On Immunology: The Wamentioning
confidence: 99%
“…The authors concluded that baseline immunity and antiviral therapy but not antithymocyte globulin treatments profoundly influence T-cell reconstitution in kidney transplant recipients. Another study of 21 subjects on preemptive therapy after SOT, who developed CMV replication episodes at a median of 4 weeks (range 2-8 weeks) after transplantation and a CMV-specific T-cell response (as determined by CMV-specific T-cell intracellular cytokine Kotton staining) at a median of 12 weeks (range 10-20 weeks), experienced a decline in the incidence of CMV replication episodes that was inversely correlated with the acquisition of the CMV-specific T-cell response (42). In addition, after acquisition of the immune response, 42 CMV replication episodes were cleared without treatment.…”
Section: Vaccines and Tailored Prevention Based On Immunology: The Wamentioning
confidence: 99%
“…However, Dþ/RÀ patients were not included (14) or represented only a minority of all patients included in these trials (10,11). Some studies showed a marked benefit of the preemptive approach in Dþ/RÀ patients (28,29), although recent studies have shown a similar or even higher incidence of CMV diseases compared to the use of antiviral prophylaxis (9,30). In a French study, 80 Dþ/RÀ kidney transplant recipients followed preemptively were compared to a historical cohort of 32 Dþ/RÀ patients who received antiviral prophylaxis (30).…”
Section: Impact Of CMV Preventionmentioning
confidence: 99%
“…26 Preemptive therapy may have a beneficial effect on the acquisition of a CMV-specific immune response. 27 Therefore, prophylaxis is associated with late-onset disease, and preemptive therapy may be protective against late-onset disease. 28 No late-onset CMV disease occurred in the present study.…”
Section: Discussionmentioning
confidence: 99%